2018
DOI: 10.3168/jds.2017-13740
|View full text |Cite
|
Sign up to set email alerts
|

Effects of prepartum dietary cation-anion difference and source of vitamin D in dairy cows: Health and reproductive responses

Abstract: The objectives of the experiment were to evaluate the effects of feeding diets with distinct dietary cation-anion difference (DCAD) levels and supplemented with 2 sources of vitamin D during the prepartum transition period on postpartum health and reproduction in dairy cows. The hypotheses were that feeding acidogenic diets prepartum would reduce the risk of hypocalcemia and other diseases, and the benefits of a negative DCAD treatment on health would be potentiated by supplementing calcidiol compared with cho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
67
4
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 66 publications
(81 citation statements)
references
References 44 publications
3
67
4
4
Order By: Relevance
“…Finally, interventions that produce a more sustained and earlier increase in blood calcium, such as feeding a prepartum diet with anionic salts to achieve a negative DCAD, would be worth investigation. A recent such study found some benefits for neutrophil function (Martinez et al, 2018). This preliminary study does not support an effect of supplemental calcium, as given to low-parity parturient cows, to improve oxidative burst or phagocytosis capacity of neutrophils.…”
Section: Short Communicationcontrasting
confidence: 60%
“…Finally, interventions that produce a more sustained and earlier increase in blood calcium, such as feeding a prepartum diet with anionic salts to achieve a negative DCAD, would be worth investigation. A recent such study found some benefits for neutrophil function (Martinez et al, 2018). This preliminary study does not support an effect of supplemental calcium, as given to low-parity parturient cows, to improve oxidative burst or phagocytosis capacity of neutrophils.…”
Section: Short Communicationcontrasting
confidence: 60%
“…Overwhelming evidence from controlled experiments support feeding acidogenic diets prepartum to reduce the risk of clinical and subclinical hypocalcemia in dairy cows (Ender et al, 1971;Dishington, 1975;Block, 1984;Martinez et al, 2018b); however, less certainty exists about the effects of acidogenic diets on lactation performance and incidence of diseases other than hypocalcemia. The current study demonstrated that reducing the DCAD of prepartum diets not only increased concentrations of tCa in blood and reduced the risk of milk fever, but it also reduced the risk of retained placenta, metritis, and the number of health events per cow in both nulliparous and parous cows.…”
Section: Discussionmentioning
confidence: 99%
“…Nutritional interventions that improve immune defenses of dairy cows are of great value for efforts to decrease antimicrobial usage and economic burden of bacterial diseases such as mastitis and metritis in dairy cows. Recent reports have documented positive effects of vitamin D in mitigation of mastitis (Lippolis et al, 2011) and metritis (Martinez et al, 2018a). In addition to the major role of vitamin D in Ca and P homeostasis, a direct immunomodulatory role of vitamin D is documented in innate immune cells (Nelson et al, 2010b;Merriman et al, 2015) and the mammary gland (Merriman et al, 2017) of cattle.…”
Section: Introductionmentioning
confidence: 99%